American Airlines and Southwest: evaluating mission statements - Micheli, Pietro (Henry Stewart Talks, 2023)
This case study looks at the (often wasted) potential impact of companies’ mission statements, especially in times of change or disruption, through a comparison of American Airlines and Southwest Airlines.